Childhood central nervous system tumours: Incidence and time trends in 13 Southern and Eastern European cancer registries. Issue 11 (July 2015) - Papathoma, Paraskevi; Thomopoulos, Thomas P.; Karalexi, Maria A.; Ryzhov, Anton; Zborovskaya, Anna; Dimitrova, Nadya; Zivkovic, Snezana; Eser, Sultan; Antunes, Luís; Sekerija, Mario; Zagar, Tina; Bastos, Joana; et al.
Abstract Aim Following completion of the first 5-year nationwide childhood (0–14 years) registration in Greece, central nervous system (CNS) tumour incidence rates are compared with those of 12 registries operating in 10 Southern–Eastern European countries. Methods All CNS tumours, as defined by the International Classification of Childhood Cancer (ICCC-3) and registered in any period between 1983 and 2014 were collected from the collaborating cancer registries. Data were evaluated using standard International Agency for Research on Cancer (IARC) criteria. Crude and age-adjusted incidence rates (AIR) by age/gender/diagnostic subgroup were calculated, whereas time trends were assessed through Poisson and Joinpoint regression models. Results 6062 CNS tumours were retrieved with non-malignant CNS tumours recorded in eight registries; therefore, the analyses were performed on 5191 malignant tumours. Proportion of death certificate only cases was low and morphologic verification overall high; yet five registries presented >10% unspecified neoplasms. The male/female ratio was 1.3 and incidence decreased gradually with age, apart from Turkey and Ukraine. Overall AIR for malignant tumours was 23/106 children, with the highest rates noted in Croatia and Serbia. A statistically significant AIR increase was noted in Bulgaria, whereas significant decreases were noted in Belarus, Croatia, Cyprus and Serbia. Although astrocytomas were overall the most common subgroup (30%) followed by embryonal tumours (26%), the latter was the predominant subgroup in six registries. Conclusion Childhood cancer registration is expanding in Southern–Eastern Europe. The heterogeneity in registration practices and incidence patterns of CNS tumours necessitates further investigation aiming to provide clues in aetiology and direct investments into surveillance and early tumour detection.